Renewable Energy Consumption and Economic Growth Nexus—A Systematic Literature Review - Bhuiyan, Miraj Ahmed; Zhang, Qiannan; Khare, Vikas; Mikhaylov, Alexey; Pinter, Gabor; Huang, Xiaowen (Frontiers in Environmental Science, 2022)
An efficient use of energy is the pre-condition for economic development. But excessive use of fossil fuel harms the environment. As renewable energy emits no or low greenhouse gases, more countries are trying to increase the use of energies from renewable sources. At the same time, no matter developed or developing, nations have to maintain economic growth. By collecting SCI/SSCI indexed peer-reviewed journal articles, this article systematically reviews the consumption nexus of renewable energy and economic growth. A total of 46 articles have been reviewed following the PRISMA guidelines from 2010 to 2021. Our review research shows that renewable energy does not hinder economic growth for both developing and developed countries, whereas, there is little significance of consuming renewable energy (threshold level) on economic growth for developed countries.